V(i)elas da memória : danças tecidas na favela do Real Parque-SP = Alleys and candles of memory: dances woven in the "Favela do Real Parque" located in São Paulo, Brazil - Santos, Cristina, 1989- (2022)
Orientadores: Daniela Gatti, Holly Elizabeth Cavrell